A new species of Helietta (Rutaceae, Pteleinae) from Colombia - Cuadros, Hermes (Phytotaxa, 2023)
Helietta hirsuta (Pilocarpinae, Galipeeae, Rutaceae), a new tree species from the dry forest remnants on the Caribbean coast of Colombia, is described, illustrated and compared with Helietta plaeana, whose name has been applied to trees found in Northeast Colombia. This new species is known from two populations in dry forest remnants in La Guajira department, and it is distinguished from the morphologically similar H. plaeana by having a pubescent full developed inflorescence longer than the leaves, rough hairs on the ovaries and puberulous young mericarps.